Pengalaman Self-Nudging dalam Relasi Komunikasi Algoritma Manusia dan Smartwatch - Patrissia, Ressa Uli; Husni, Mochamad (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This study examines users’ subjective experiences of algorithmic communication generated by smartwatches in the context of health decision-making. Using a critical phenomenological approach and an Interpretative Phenomenological Analysis (IPA) design, the study involved 12 active smartwatch users from urban areas in Indonesia who had used health-notification features for more than six months. Data were collected through in-depth interviews, digital observation, and reflective journaling. Findings reveal that smartwatch notifications function not merely as reminders but subtly and repeatedly shape users’ behaviors and health decisions, often without deliberate reflection. The concept of self-nudging, ideally grounded in user autonomy, frequently shifts into pseudo-self-nudging and even algorithmic steering, where the algorithm becomes the dominant agent guiding user actions. Users experience ambivalence—feeling supported yet simultaneously controlled—indicating a shift in bodily authority from personal intuition to algorithmic recommendations. These findings highlight the need for algorithmic literacy and ethical design in wearable technologies to ensure that users retain agency and reflective awareness when facing digital interventions that are prescriptive and normative.